Examination of Structures Built with Tunnel Formwork in Terms of Strength and Cost according to the Earthquake Regulations of 2007 and 2018 - Yilmaz Dilek; Abdulhalim Karasin (Advances in Civil Engineering)
Turkey has always been exposed to active fault lines passing through and unpredictable seismic activities. These ground movements have always been one of the important issues in our country, which have led to great destruction and loss of lives and property in its past. For this reason, our earthquake regulations, which aim to design more accurately against earthquake movements, are continuously made improvements. In this study, the analysis of structures built with tunnel formwork system which is popular today with the new earthquake regulations entered into force in 2018, and the strength and cost according to the old earthquake regulation in terms of what differences will occur. In addition to the study, we investigated how the number of floors and regular floor plans affects the results. For this purpose, two types of structures were covered with 5, 10, and 15 storey models created, first in the 2007 earthquake regulation; then, in the 2018 earthquake regulation, design analysis was carried out. As a result, the new earthquake regulation, which came into force in 2018, led to more realistic results as it provides more accurate environmental inputs used in design analysis. Earthquake loads affecting floors increased by 3.9% for 5 storey in regular structures, decreasing by 38.4% for 10 stories and 43.3% for 15 stories. More irregular structures increased 7.3% for 5 storey, 10-storey structures decreased by 38.9%, and 15-storey structures decreased by 43.6%. In terms of cost, there was a 0.07% increase in total cost in 5-storey buildings, 2.45% in 10-storey buildings, and a 3.91% reduction in 15-storey buildings. In addition to these results, an empirical formula that estimates m2 prices depending on the number of floors was obtained.